2011
DOI: 10.5665/sleep.1238
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Association between Short Sleep, Body Weight, and Emotional and Learning Problems in Hispanic and Caucasian Children

Abstract: Children with reduced amounts of sleep (≤ 7.5 h/night) had an increased risk for higher body weight in early adolescence. Similarly, children who slept ≤ 7.5 h/night had higher risk of being anxious or depressed or having learning problems in early adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
102
4
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(113 citation statements)
references
References 47 publications
3
102
4
4
Order By: Relevance
“…10 Similarly, Silva et al recruited 304 children (aged 6-12) who were followed-up 5 years later (aged 10 to 18), and observed that sleeping for ,7.5 hours per day at baseline, compared with $9.0 hours per day at baseline, was associated with a threefold increased likelihood of being obese at follow-up. 11 Our findings are consistent with these findings and extend the research by following adolescents over a longer time period and studying the entire BMI distribution. However, 1 study reported a null association between sleep duration and BMI defined obesity at 2-year follow-up in a sample of 13 568 adolescents.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…10 Similarly, Silva et al recruited 304 children (aged 6-12) who were followed-up 5 years later (aged 10 to 18), and observed that sleeping for ,7.5 hours per day at baseline, compared with $9.0 hours per day at baseline, was associated with a threefold increased likelihood of being obese at follow-up. 11 Our findings are consistent with these findings and extend the research by following adolescents over a longer time period and studying the entire BMI distribution. However, 1 study reported a null association between sleep duration and BMI defined obesity at 2-year follow-up in a sample of 13 568 adolescents.…”
Section: Discussionsupporting
confidence: 81%
“…Three longitudinal studies have investigated the relationship between sleep duration and adolescent BMI. [9][10][11] Two of those studies found evidence that less sleep led to an increased likelihood of being classified as obese at follow-up, 10,11 whereas 1 study found no association. 9 These studies only measured BMI at 2 time points and categorized participants into nonobese and obese groups based on BMI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations